Non - immune hydrops fetalis and cytornegalovirus intrauterine infection - Acho, Segundo (2015)
We report a case of non-immune hydrops and intrauterine cytomegalovirus infection is reported. Dropsy was diagnosed by ultrasound at 31 weeks of gestational age. Ultrasonographic features of the intrauterine fetal hydrops and newborn described. Other evaluations and studies to determine associated malformations was performed, which is discarded confirmed the suspected diagnosis of cytomegalovirus infection and fetal hydrops.